Artificial Intelligence in Arabic Writing Instruction: Students’ Lived Experiences in Learning Maharah al-Kitabah - Agus Alfaya Arif; Adhi Setiyawan; Dudung Hamdun (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
Writing skills are increasingly marginalized in the rise of digital literacy practices. The rapid growth of Artificial Intelligence (AI) has not yet been accompanied by a well-established cyber-pedagogical framework capable of maintaining students’ independent writing competencies. This study aims to explore the lived experiences of Arabic Language Education students in utilizing AI within maharah al-kitabah learning and to analyze its implications for writing proficiency and academic ethics. A qualitative phenomenological approach was applied through semi-structured interviews with 23 students actively using AI-based applications in Arabic writing activities. The findings reveal that AI is perceived as a cognitive support tool that assists students in generating ideas, improving grammatical structures, enriching vocabulary, and enhancing coherence and writing fluency. However, students also acknowledge the risks of dependency and reduced critical thinking if AI is used without proper pedagogical guidance. These results underline the need for a reflective and ethically grounded integration of AI in maharah al-kitabah instruction to ensure sustainable development of independent writing skills.